After Steve : how Apple became a trillion-dollar company and lost its soul - Mickle, Tripp (London : HarperCollinsPublishers, 2022)
Examines the path of Apple after the death of Steve Jobs and how the selection of Tim Cook as his successor led to the prioritization of revenue growth over innovation.
One more thing -- The artist -- The operator -- Keep him -- Intense determination -- Fragile ideas -- Possibilities -- Can't innovate -- The crown -- Deals -- Blowout -- Pride -- Out of fashion -- Fuse -- Accountants -- Security -- Hawaii days -- Smoke -- The Jony 50 -- Power moves -- Not working -- A billion pockets -- Yesterday.
Includes bibliographical references (pages 477-479) and index.
Keywords: Cook, Timothy D; Ive, Jonathan; Cook, Timothy D; Ive, Jonathan; Apple Computer, Inc; Apple Computer, Inc. -- History; Apple Computer, Inc; Computer industry -- United States -- History; Informatique -- Industrie -- États-Unis -- Histoire; Computer industry; United States; History